Pelatihan pembuatan dan pengelolaan website untuk Remaja Dusun Terban (FRISTA) di era digitalisasi - Sanjaya, Intan Winda Widya; Safi’i, Muhammad; Rahmawati, Avinda; Asih , Winda Kurnia; Kurniawati , Berta (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
Websites are one of the information technologies that can be easily found online. The website presents internet users with various information, services, products, or content. Website creation can be done for a fee or for free. Knowledge of information technology is essential for young people (teenagers). However, none of the youth in Terban Hamlet know about website development. Therefore, Terban Hamlet does not yet have a Hamlet website as one of the media to broadcast information and Hamlet activities. Therefore, training on website creation and management is needed for the youth of Terban Hamlet. The purpose of the activity is to train Terban Hamlet teenagers in creating and managing websites using the WordPress Content Management System (CMS). This activity was carried out directly with the participation of 12 "FRISTA" teenagers. Making a website begins with a needs survey, followed by preparation and making materials. The survey is carried out offline and ends with a question-and-answer session. The output of this training is that teenagers in Terban Hamlet (FRISTA) can create and manage Hamlet's websites and personal websites.